Concordance of HPV genotype detection in cervical and urine samples among cervical cancer screen positive women - Nihar, Fatema; Ferdous, Jannatul; Ara, Rowson; Khatoon, Farhana; Meher, Subrina; Akter, Naznine; Akther, Moushume; Naher, Syfun (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2024)
Background: This study investigates the concordance of HPV genotype detection in urine and cervical samples among women undergoing cervical cancer screening. Methods: Conducted over one year at the Department of Gynaecological Oncology, BSMMU, Dhaka, the study enrolled 74 women aged 30-60 years with positive visual inspection with acetic acid (VIA) results or abnormal Pap test findings. Urine samples (20 ml) and cervical samples were collected from each participant. The samples were analyzed using multiplex real-time PCR to amplify high-risk HPV types (16, 18, and others). DNA was extracted using the Qiagen viral DNA extraction kit. Sensitivity and specificity of HPV detection in urine samples were compared to cervical sampling, the gold standard. Data were analyzed with SPSS 22.0, and agreement was assessed using the Kappa index. Results: In this study of 74 participants, HPV detection and genotype distributions were compared between cervical and urine samples. The mean age was 40.07 years, with 89.2% of participants being married and 75.7% multipara. There was moderate agreement between HPV detection in cervical and urine samples (Kendall’s tau = 0.752, p<0.001). Cervical samples identified a greater variety of HPV types, including HPV 16 and high-risk (HR) genotypes, compared to urine samples. The Cohen’s Kappa coefficient for agreement was 0.746 (p<0.001), indicating moderate concordance. Overall, cervical sampling demonstrated higher sensitivity for HPV detection. Conclusions: The study demonstrates moderate concordance between cervical and urine samples in HPV detection, with cervical sampling showing higher sensitivity for identifying HPV genotypes.